Therapeutic literature as a healing tool: psychological potential - CHERNYSH, Oksana; OKSIUTOVYCH, Maryna; KHARYTONOVA, Nataliya; MATEYUK, Oleg (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
The article examines therapeutic literature as an effective tool for psychological healing in the context of the modern world, characterized by high levels of stress and psychological challenges. Various types and forms of therapeutic literature, including fairy tale therapy, bibliotherapy, poetic therapy, cognitive-oriented literature, therapeutic metaphors, motivational, and educational literature, are analyzed. Their advantages and limitations in the context of psychological impact are identified. Particular attention is paid to the analysis of fairy tale therapy as a method that uses symbolic images to process profound emotional experiences, and bibliotherapy, which promotes self-discovery through reading fiction and motivational literature. Additionally, the study reveals the potential of therapeutic literature in emotional support, self-discovery, the development of empathy, and cognitive skills. The importance of a qualified approach to the use of therapeutic texts, which requires specialists to combine literary and psychological knowledge, as well as skills in working with text and therapeutic influence, is emphasized. The role of the specialist, their competencies, skills, and ethical aspects of working with therapeutic literature, including the need for individualization of approach and consideration of cultural differences, are considered. The article highlights the challenges faced by specialists, including the limitations of application of therapeutic literature and the need to integrate it with other methods of psychological assistance. It emphasizes the importance of continuous learning and reflection to ensure the efficacy of the therapeutic process. Prospects for further research in the field of therapeutic literature are identified, including the study of the effectiveness of various types of literature for specific psychological issues, the development of training programs for specialists, the examination of the impact of cultural factors, and the use of digital technologies to expand access to therapeutic literature.